The Care Debate During the First Covid Lockout in Barcelona. - Natalia Ribas Mateos; Encarna Herrera-Martínez (Journal of Aging Research And Healthcare, 2023)
The debate of care uses the role of different actors from the interpretation of the debates and discussion groups carried out during the fieldwork. We identify here: the elderly person, the caregivers - here in this article in their wide variety, from family members to hired workers, especially immigrant women- and thirdly, as the third aspect of the triangle, and which remains in this chapter more blurred, from municipal and health public services. This care triangle is also very affected by the adverse effects of the pandemic.The pandemic highlights the existing systemic equalities, particularly affecting migrant women and ethnic minorities, people who work in the care sector and health personnel.
Keywords: carers